Managing the oil revenue boom : the role of fiscal institutions - Ossowski, Rolando; International Monetary Fund. (Washington, DC : International Monetary Fund, 2008)
This bok examines the fiscal responses of oil-producing countries to the recent oil boom through to 2005 and the role of special fiscal institutions-oil funds, fiscal rules and fiscal responsibility legislation, and budgetary oil prices-in fiscal management in oil-producing countries, and draws some general lessons.
Introduction -- The recent oil boom -- Special fiscal institutions and the management of oil revenue : recent international experience -- Quantitative assessment of the impact of fiscal institutions on fiscal outcomes -- A framework for strengthening fiscal institutions in oil-producing countries.
Includes bibliographical references.
aug 09/05/13
Loans
Keywords: Petroleum industry and trade -- Economic aspects; Fiscal policy